How to apply the movement disorder society criteria for diagnosis of progressive supranuclear palsy. Issue 8 (18th March 2019) - Grimm, Max‐Joseph; Respondek, Gesine; Stamelou, Maria; Arzberger, Thomas; Ferguson, Leslie; Gelpi, Ellen; Giese, Armin; Grossman, Murray; Irwin, David J.; Pantelyat, Alexander; Rajput, Alex; Roeber, Sigrun; et al.
Abstract: Background: The Movement Disorder Society criteria for progressive supranuclear palsy define diagnostic allocations, stratified by certainty levels and clinical predominance types. We aimed to study the frequency of ambiguous multiple allocations and to develop rules to eliminate them. Methods: We retrospectively collected standardized clinical data by chart review in a multicenter cohort of autopsy‐confirmed patients with progressive supranuclear palsy, to classify them by diagnostic certainty level and predominance type and to identify multiple allocations. Results: Comprehensive data were available from 195 patients. More than one diagnostic allocation occurred in 157 patients (80.5%). On average, 5.4 allocations were possible per patient. We developed four rules for Multiple Allocations eXtinction (MAX). They reduced the number of patients with multiple allocations to 22 (11.3%), and the allocations per patient to 1.1. Conclusions: The proposed MAX rules help to standardize the application of the Movement Disorder Society criteria for progressive supranuclear palsy. © 2019 International Parkinson and Movement Disorder Society